Cartography and analysis of the urban growth, case study: Inter-communal grouping of Batna, Algeria - Fekkous, Nadia; Alkama, Djamel; Fekkous, Khaoula (Quaestiones Geographicae, 2023)
This paper focuses on the analysis of the urban macroform in terms of urban compactness and dispersion (urban sprawl) in the inter-communal grouping of Batna, which is composed of four adjacent interconnected commu- nal districts: Batna, Tazoult, Oued Chaaba and Fesdis. First, the urban macroform is examined by mapping the urban areas that are characterised by morphological changes over a period of 36 years utilising remote sensing and geograph- ic information system (GIS) through satellite images taken from Landsat TM and ETM +, Sentinel 2 (1984, 1996, 2008 and 2020). Next, the Shannon entropy method is utilised to determine compactness or dispersion of urban growth over time. In addition, a fractal analysis based on the box-counting method is used to assess the complexity and to explain the morphological reality of the macroform through urban changes. In order to predict the future change scenarios and spatial distributions of land use and land cover in the coming years the hybrid cellular automata (CA) – Markov method is used. The results of the remote sensing, Shannon entropy values and fractal indices demonstrate that Batna inter-municipal grouping has experienced moderate urban development according to the observed urban sprawl be- tween 1984 and 2020. These data are helpful in the urban planning and to provide decision-making tools.